Association Between Three eNOS Polymorphisms and Intracranial Aneurysms Risk. Issue 4 (January 2015) - Yang, Chao; Qi, Zhen-yu; Shao, Chuan; Xing, Wei-kang; Wang, Zhong; Hua-Xiang Xia., Harry
<x xml:space="preserve">Abstract</x> Abstract Endothelial nitric oxide synthase (eNOS) is the catalyst of endothelial nitric oxide (NO) synthesis. Polymorphisms in the eNOS gene may influence the risk of intracranial aneurysm (IA), but the results of existing researches are still inconsistent. Thus, we performed the present meta-analysis to derive a more precise estimation between eNOS polymorphisms (T786C, G894T, 27-bp-variable number of tandem repeat [VNTR]) and IA risk. Case–control studies evaluating the association between the eNOS polymorphisms and IA risk were searched in PubMed, Ovid & Embase, Web of Science, and Chinese Wanfang datasets with the last search up to July 15, 2014. The pooled odds ratios (ORs) for the association between eNOS polymorphisms and IA and their corresponding 95% confidence intervals (CIs) were estimated using the random or fixed-effects model. Finally, 10 studies for T786C polymorphism (1819 cases and 1893 controls), 9 studies for G894T polymorphism (1393 cases and 1508 controls), and 7 studies for 27-bp-VNTR polymorphism (1281 cases and 1406 controls) were included in the meta-analyses. In the overall analysis, no evidence of association between eNOS polymorphisms and susceptibility of IA was found. When subgrouped by race descent, significantly increased risk was detected among Asians for T786C polymorphism (heterozygous comparison of codominant model: OR = 1.294, 95% CI = 1.025–1.634; dominant model: OR = 1.277, 95% CI = 1.019–1.600), but not in Caucasians or the other 2 polymorphisms. Our meta-analysis suggested that T786C polymorphism was associated with increased risk of IA among Asians, whereas G894T and 27-bp-VNTR polymorphisms might have no influence on the susceptibility of IA.